Remote Sensing Image On‐Demand Computing Schema for the China ZY‐3 Satellite Private Cloud‐Computing Platform. (16th November 2014) - Guo, Wei; She, Bing; Zhu, Xinyan
Abstract: Time is a crucial factor for many remote sensing applications such as emergency response. The traditional approach requires users to spend a lot of time downloading, processing, and viewing satellite images with specialized software. Realizing interactive real‐time processing and visualization of satellite images online is our focus. This article presents an On‐Demand computing schema for remote sensing images. A processing chain model is proposed for satellite images on a private cloud computing platform designed for the China Centre for Resources Satellite Data and Application (CCRSDA). The architecture, processing flow, optimization method, fault tolerance, and user interface are described in detail. To test the efficiency and scalability of the platform, 11 processing chains were created and three load balance experiments were executed. The results from these experiments show the validity of the proposed methods and architecture.